1998
DOI: 10.1074/jbc.273.9.5137
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Fibroblast Collagenase (Matrix Metalloproteinase-1)Gene Expression by Ceramide Is Mediated by Extracellular Signal-regulated and Stress-activated Protein Kinase Pathways

Abstract: Inflammatory cytokines tumor necrosis factor-␣ and interleukin-1 trigger the ceramide signaling pathway, initiated by neutral sphingomyelinase-elicited hydrolysis of cell membrane phospholipid sphingomyelin to ceramide, a new lipid second messenger. Here, we show that triggering the ceramide pathway by sphingomyelinase or C 2 -and C 6 -ceramide enhances collagenase-1 (matrix metalloproteinase-1; MMP-1) gene expression by fibroblasts. C 2 -ceramide activates three distinct mitogen-activated protein kinases (MAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
182
1
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 202 publications
(202 citation statements)
references
References 52 publications
17
182
1
1
Order By: Relevance
“…This observation is in agreement with recent studies with PD98059, demonstrating that ERK1,2 pathway mediates activation of MMP-1 expression in ®broblasts (Reunanen et al, 1998;Westermarck et al, 1998) and MMP-9 expression in transformed keratinocytes (Gum et al, 1997). Interestingly, a recent study demonstrated that IFN-g inhibits TGF-b signaling in ®brosarcoma cells by inducing expression of SMAD7, an inhibitory member of the SMAD transcription factor family (Ulloa et al, 1999).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This observation is in agreement with recent studies with PD98059, demonstrating that ERK1,2 pathway mediates activation of MMP-1 expression in ®broblasts (Reunanen et al, 1998;Westermarck et al, 1998) and MMP-9 expression in transformed keratinocytes (Gum et al, 1997). Interestingly, a recent study demonstrated that IFN-g inhibits TGF-b signaling in ®brosarcoma cells by inducing expression of SMAD7, an inhibitory member of the SMAD transcription factor family (Ulloa et al, 1999).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, overexpression of tissue inhibitor of metalloproteinases (TIMP)-1, -2, and -3 appears an e ective way of inhibiting the invasion of malignant cells . Our results together with recent observations (Reunanen et al, 1998;Ravanti et al, 1999;Westermarck et al, 1998;Gum et al, 1997) indicate that modulation of the activity of distinct MAPKs may serve as a potent way of inhibiting MMP expression and invasion. In conclusion, the results of the present study show that selective activation of the IFN-g signaling pathway may serve as a speci®c way of potently suppressing invasion and metastasis of malignant squamous epithelial cells in vivo.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…For instance, p38 might play an important role in phorbol ester-induced type IV collagenase production by a squamous cell carcinoma cell line as well as in cytokine-stimulated chondrocytes (27,28). ERK and JNK have been implicated in the regulation of collagenase gene expression in cultured fibroblasts (29). In contrast to FLS, collagenase and stromelysin gene expression in endothelial cells are dependent on p38 (30).…”
Section: Figurementioning
confidence: 99%
“…23 Northern blot hybridizations were performed as described previously 24 with cDNAs labeled with [␣-32 P]-dCTP using random priming. A 1.5 kb cDNA was used for MMP-19 7 detection.…”
Section: Northern Analysismentioning
confidence: 99%